Solubility of 3-chloro-N-phenylphthalimide in ten organic solvents from T = (288.15 to 323.15) K: Determination and modelling. (May 2016) - Du, Cunbin; Xu, Renjie; Han, Shuo; Xu, Jian; Meng, Long; Wang, Jian; Zhao, Hongkun
Graphical abstract: Highlights: Solubility of 3-chloro- N -phenylphthalimide in ten solvents were determined. The solubility were correlated with four models. The solution properties were evaluated. Abstract: The solubility of 3-chloro -N -phenylphthalimide in acetonitrile, methanol, n -propanol, isopropanol, n -butanol, 2-methyl-1-propanol, ethyl acetate, acetone, 1, 4-dioxane and acetic acid were obtained experimentally with the high-performance liquid chromatography analysis at temperature ranging from (288.15 to 323.15) K under 0.1 MPa. The solubility values of 3-chloro- N -phenylphthalimide in those solvents increased with an increase in temperature, and decreased from high to low based on the following order: 1, 4-dioxane > acetone > ethyl acetate > acetonitrile > acetic acid > ( n -propanol, n -butanol) > (methanol, 2-methyl-1-propanol) > isopropanol. The obtained solubility data of 3-chloro- N -phenylphthalimide in the studied solvents were correlated by using four models, the modified Apelblat equation, λh equation, Wilson model and NRTL model. The calculated solubility using the modified Apelblat equation provided better agreement with those evaluated by the other three models. In general, the four models were all acceptable for correlating the solubility data of 3-chloro- N -phenylphthalimide in the studied solvents. In addition, the change of molar Gibbs energy, molar solution enthalpy, molar solution entropy and excess enthalpy of the solution for per 1 mol of mixture of 3-chloro- N -phenylphthalimide in these solvents were evaluated at mean harmonic temperature. The dissolution process of 3-chloro- N -phenylphthalimide in the selected solvents was exothermic and entropy-driving. The study concerning the solubility of 3-chloro- N -phenylphthalimide in the selected solvents and solution properties can provide fundamental data in the manufacturing and separating process of 3-chloro- N -phenylphthalimide.